2019
DOI: 10.1371/journal.pone.0214574
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Leishmania (Viannia) braziliensis infection on the attractiveness of BALB/c mice to Nyssomyia neivai (Diptera: Psychodidae)

Abstract: Background Phlebotomine sand flies are vectors for several pathogens, with Leishmania being the most important. In Brazil, the main aetiological agent of American cutaneous leishmaniasis (ACL) is Leishmania (Viannia) braziliensis , and Nyssomyia neivai is one of its main vectors in São Paulo state and other areas of South America. Similar to other haematophagous insects, sand flies use volatile compounds called kairom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…However, there is evidence that the effect may not be universal e.g. there was no significant difference in the attractiveness of the sand fly Nyssomyia neivei toward BALB/c mice infected with Leishmania braziliensis and uninfected mice [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that the effect may not be universal e.g. there was no significant difference in the attractiveness of the sand fly Nyssomyia neivei toward BALB/c mice infected with Leishmania braziliensis and uninfected mice [43].…”
Section: Discussionmentioning
confidence: 99%
“…More tsetse flies (Glossina pallidipes) bit the Orma Boran oxen infected with Trypanosoma congolense, but not those infected by Trypanosoma vivax (Baylis and Nambiro, 1993;Baylis and Mbwabi, 1995), and only hybrids of the Triatoma dimidiata complex preferred Trypanosoma cruzi-infected mice over uninfected ones (Ramirez-Sierra and Dumonteil, 2016). Leishmania infantum made their hamster hosts more attractive to Lutzomyia longipalpis (O'Shea et al, 2002;Nevatte et al, 2017), but Leishmania braziliensis did not enhance attractiveness of mice for Nyssomyia neivai (da Rocha Silva et al, 2019). The probability that a bat fly chose a host was negatively Turell et al, 1984 33 Aedes taeniorhynchus…”
Section: Empirical Evidence Of Parasite Manipulation Of Host Attractimentioning
confidence: 99%
“…Host manipulation by parasites has been fascinating parasitologists for decades (Thomas et al, 2005), especially when this manipulation results in dramatic changes in host's physiology (Cordaux et al, 2011;Kageyama et al, 2012;Fayard et al, 2020), morphology (Bakker et al, 1997;Yanoviak et al, 2008;Fayard et al, 2020) or behavior (Berdoy et al, 2000;Thomas et al, 2002;Weinersmith, 2019;Fayard et al, 2020). This host exploitation strategy, described in many phylogenetically distant host-parasite systems, usually involves phenotypic changes in the infected host (extended phenotype, Dawkins, 1982). These alterations can be mediated by direct or indirect mechanisms (Thomas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, usually focussed to a single sand y species, have reported a blood meal size in a wide range from 0.4 to more than 1.0 mg of ingested blood [3,7,[10][11][12][13][14][15]. However, the broad spectrum of used method makes precise interspeci c comparison di cult.…”
Section: Introductionmentioning
confidence: 99%